Workplace learning: learning experiences of pre-clerkship students in their clinical learning environment at a medical university in UAE - Nooreen Adnan,; Syeda Rubaba Azim,; Farah Azhar,; Lubna Ahmed,; Pankaj Lamba, (Journal of the Pakistan Medical Association, 2023)
Objective: To explore how students in the pre-clerkship phase perceive the workplace clinical learning environment based on their experiential learning and social participation. Method: The cross-sectional study was conducted at the Gulf Medical University, United Arab Emirates in June 2019 and comprised 2nd and 3rd year medical students. Data was collected using the undergraduate clinical education environment measure tool which is a valid and reliable instrument to measure clinical learning environment for undergraduate medical students. Results: There were 858 students, and 70.3% of the students expressed satisfaction with clinical learning environment categories. Conclusion: The average satisfaction level of the students regarding the quality of supervision was better than that of workplace environment and learning opportunities provided. Key Words: Clinical learning environment, UCEEM, Medical students, Clinical workplace, Supervision quality, Learning opportunities, Feedback.